A Comprehensive Approach to Parkinson’s Disease: Addressing Its Molecular, Clinical, and Therapeutic Aspects - Muleiro Alvarez, Mauricio (2024)
Parkinson’s disease (PD) is a gradually worsening neurodegenerative disorder affecting the nervous system, marked by a slow progression and varied symptoms. It is the second most common neurodegenerative disease, affecting over six million people in the world. Its multifactorial etiology includes environmental, genomic, and epigenetic factors. Clinical symptoms consist of non-motor and motor symptoms, with motor symptoms being the classic presentation. Therapeutic approaches encompass pharmacological, non-pharmacological, and surgical interventions. Traditional pharmacological treatment consists of administering drugs (MAOIs, DA, and levodopa), while emerging evidence explores the potential of antidiabetic agents for neuroprotection and gene therapy for attenuating parkinsonian symptoms. Non-pharmacological treatments, such as exercise, a calcium-rich diet, and adequate vitamin D supplementation, aim to slow disease progression and prevent complications. For those patients who have medically induced side effects and/or refractory symptoms, surgery is a therapeutic option. Deep brain stimulation is the primary surgical option, associated with motor symptom improvement. Levodopa/carbidopa intestinal gel infusion through percutaneous endoscopic gastrojejunostomy and a portable infusion pump succeeded in reducing “off” time, where non-motor and motor symptoms occur, and increasing “on” time. This article aims to address the general aspects of PD and to provide a comparative comprehensive review of the conventional and the latest therapeutic advancements and emerging treatments for PD. Nevertheless, further studies are required to optimize treatment and provide suitable alternatives.